2002
DOI: 10.1074/jbc.m202435200
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-2 Mediates Adhesion and Proliferation of Colon Carcinoma Cells

Abstract: Syndecan-2 is a transmembrane heparan sulfate proteoglycan whose function at the cell surface is unclear. In this study, we examined the function of syndecan-2 in colon cancer cell lines. In several colon cancer cell lines, syndecan-2 was highly expressed compared with normal cell lines. In contrast, syndecan-1 and -4 were decreased. Cell biological studies using the extracellular domain of recombinant syndecan-2 (2E) or spreading assay with syndecan-2 antibody-coated plates showed that syndecan-2 mediated adh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
130
0
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 155 publications
(140 citation statements)
references
References 40 publications
6
130
0
4
Order By: Relevance
“…Normal colon epithelial cells did not express SDC2, whereas colon carcinoma cells showed SDC2 up-regulation resulting in an increased SDC2 expression that proved crucial for tumourigenicity. 9,11,14 Park et al 14 showed SDC2 to be necessary for cell-cycle progression and cell-matrix interaction in colon cancer cells. Moreover, an increased level of SDC2 led to a less adhesive phenotype and loss of contact inhibition.…”
Section: Syndecan-2 In Prostate Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Normal colon epithelial cells did not express SDC2, whereas colon carcinoma cells showed SDC2 up-regulation resulting in an increased SDC2 expression that proved crucial for tumourigenicity. 9,11,14 Park et al 14 showed SDC2 to be necessary for cell-cycle progression and cell-matrix interaction in colon cancer cells. Moreover, an increased level of SDC2 led to a less adhesive phenotype and loss of contact inhibition.…”
Section: Syndecan-2 In Prostate Cancermentioning
confidence: 99%
“…7 Early recognizable role of SDC2 was cell adhesion and migration, but recently SDC2 has also been implicated in the tyrosine kinase signalling pathway activation, cancer progression, and angiogenesis. [8][9][10][11][12] Several studies investigated the role of SDC2 in different carcinomas; [13][14][15] however, only one was focused on SDC2 in prostate cancer. 16 SDC2 expression and relationship with established prognostic features were assessed in a cohort of 86 patients treated with radical prostatectomy for clinically localized prostate adenocarcinoma to determine the expression and prognostic value of SDC2 in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…The activities of the extracellular domain also extend to other syndecans. Colon carcinoma cells plated in serum are induced to round up and detach when treated with soluble extracellular domain of syndecan-2, presumably because the soluble ectodomain disrupts an adhesion complex at the cell surface (8). Additionally, fibroblast growth factor 2-stimulated proliferation in the developing wing bud and cultured chondrocytes is blocked by antibodies against the syndecan-3 extracellular domain, suggesting a role for this protein domain in the assembly of the fibroblast growth factor 2 signaling complex (18,19).…”
mentioning
confidence: 99%
“…Syndecan expression has been reported to be altered during tumorigenesis and disease progression (30,36,39), enhancing interest in syndecan family heterodimerization. Analyzing the role of the conserved phenylalanine in heterodimerization may be useful in assessing the mechanism underlying these interactions and determining strategies to inhibit syndecan heterodimers.…”
Section: Discussionmentioning
confidence: 99%